2012
DOI: 10.1166/jnn.2012.6435
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Gd@C82-PVK and C60-PVK–A Kind of Fullerene-Grafted Polymer

Abstract: Different fullerene-grafted poly(N-vinylcarbazole) was synthesized by free radical polymerization and the influence of the amount of initiator, the reaction time and the reaction temperature on the polymerization was studied. Metallofullerene-grafted polymer (Gd@C82-PVK) was firstly synthesized and characterized by GPC, UV-vis, FTIR, DSC, XPS. The results demonstrated that the fullerenes had chemically combined with PVK. Fluorescence spectra suggested that the grafted fullerenes had certain influence on the fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Recently, free-radical polymerization of poly-N-vinylcarbazone (7) with either C 60 or Gd@C 82 was performed to synthesize the corresponding polymer-grafted fullerene derivatives. 31 Spectroscopic studies confirmed the covalent attachment of the fullerene species. Fluorescence spectra suggested that the covalently grafted fullerenes had certain influences on the fluorescence properties of the polymer.…”
Section: Radical Reactionmentioning
confidence: 76%
“…Recently, free-radical polymerization of poly-N-vinylcarbazone (7) with either C 60 or Gd@C 82 was performed to synthesize the corresponding polymer-grafted fullerene derivatives. 31 Spectroscopic studies confirmed the covalent attachment of the fullerene species. Fluorescence spectra suggested that the covalently grafted fullerenes had certain influences on the fluorescence properties of the polymer.…”
Section: Radical Reactionmentioning
confidence: 76%
“…M@C 2v (9)‐C 82 (M=rare‐earth metals) is one of the most abundant metallofullerene species that have been studied extensively [1a,d] . Typical exhohedral reactions of M@C 82 , such as radical addition reactions, [4] Diels‐Alder reactions, [5] Bingel‐Hirsch reactions [6] and 1,3‐dipolar cycloaddition reactions, [7] have been utilized to produce covalent derivatives of M@C 82 . Diels‐Alder reactions of La@C 82 with cyclopentadiene (Cp) and 1,2,3,4,5‐pentamethylcyclopentadiene (Cp*) have been studied previously [5] .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, synthesis of many endohedral metallofullerenes (EMFs) [1] that encapsulate Li [2], La [3][4][5], Sc [6,7], Gd [8,9], Yb [10,11], Ba [12], and Sm [13] have been reported. It is expected that EMFs encapsulating Gd atom(s) or Gd@C 82 [8,9] can be used as contrast agents in magnetic resonance imaging (MRI) owing to the increased stability of the Gd (III) ion, minimal toxic effects, high solubility in water, and high proton relaxivity [14]. Metal-fullerene complexes, which include Os [15,16], Zn [17], and Co [18] are also important in fullerene chemistry because of their potential applications in biological, magnetic, electronic, catalytic, and optical devices.…”
Section: Introductionmentioning
confidence: 99%